STRATEGI PEMERINTAH TERHADAP PENGEMBANGAN OBJEK WISATA ALAM DI DESA TANA TORO KECAMATAN PITU RIASE KABUPATEN KABUPATEN SIDENRENG RAPPANG - Hasmiati; Ibrahim, Monalisa; Sapri (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
This research aims to determine the government's strategy for developing natural tourist attractions in Tana Toro village, Pitu Riase subdistrict, Sidenreng Rappang district. The population in this study was 579 people with 85 samples. The research method uses quantitative descriptive, data collection techniques, observation, literature study and questionnaires, the data analysis techniques used are descriptive statistical analysis, data quality testing (validity & reliability testing), simple linear regression analysis and hypothesis testing using the SPSS26.0 application. The results of this research show that 58% of the average percentage of government strategies in Tana Toro village, Pitu Riase subdistrict, Sidenreng Rappang district is in the